Effectiveness and Safety of Ultrasound Guided Lower Extremity Nerve Blockade in Infragenicular Bypass Grafting for High Risk Patients With Chronic Limb Threatening Ischaemia. (August 2019) - Kikuchi, Shinsuke; Yamaguchi, Takuya; Miyake, Keisuke; Uchida, Daiki; Koya, Atsuhiro; Iida, Takafumi; Kurosawa, Atsushi; Sasakawa, Tomoki; Kunisawa, Takayuki; Azuma, Nobuyoshi
Abstract : Objectives: Surgical revascularisation to accomplish limb salvage remains preferable in some patients with chronic limb threatening ischaemia (CLTI). The aim of this study was to evaluate the effectiveness and safety of ultrasound guided lower extremity nerve blockade (UGNB) in infragenicular bypass surgery (IGBS). Methods: This was a single centre, retrospective clinical study. Fifty-nine patients with CLTI (67 limbs) who underwent IGBS under UGNB (femoral and sciatic nerve blockade) at Asahikawa Medical University between January 2012 and December 2017 were compared with patients with CLTI (137 limbs) who underwent IGBS under general anaesthesia (GA) over the same period. Propensity score matching based on pre-operative comorbidities was used to minimise background differences of the two groups. Results: Fifty-six pairs of CLTIs were matched and analysed (55% dialysis dependent). Procedure duration was similar between the two groups, but intraoperative catecholamine index and intravenous fluid volume were lower with UGNB compared with GA (2.9 ± 4.6 vs. 5.9 ± 6.5; p < .01 and 1831 ± 990 vs. 2335 ± 931 mL; p < .01, respectively). The mean arterial blood pressure during induction of anaesthesia was significantly decreased with GA. Post-operatively, the time period to resume a clear liquid and solid food diet was significantly shorter with UGNB (P<0.01 for both outcome measures). Intravenous fluid volume was significanlty lower, while cardiac complications and delirium, based on the NEECHAM confusion scale, occurred significantly less often with UGNB than GA. These significant differences show advantages of UGNB compared to GA. No mortality or major amputations were observed in either group. Early graft thrombosis was observed in five limbs (8.9%) with UGNB and in four limbs with GA (7.1%) ( p = .73). Conclusions: UGNB has advantages for intra- and post-operative management and could be a useful method to prevent peri-operative complications for high risk patients with CLTI. To ensure the effectiveness of UGNB for IGBS for future indications, a randomised study is required.